Influence of polarization azimuth on twophoton absorption in CdS - Kulish, N.R.; Lisitsa, M.P.; Malysh, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
To study the dependence of the two-photon absorption coefficient β on a polarization azimuth ϕ we used the method of one light source at the ruby laser frequency. It was shown that β changes smoothly with increasing ϕ from zero to π/2. The minimum value of β was realized in the vicinity of ϕ = 45°.